A case study on the application of cognitive strategies to Malay Mandarin learners / Lew Ya Ling - Lew, Ya Ling (Universiti Teknologi MARA, Perlis, 2020)
Through questionnaire survey and interview, this research analyzes the cognitive strategies application of Universiti Teknologi MARA Perlis Malay students during their Mandarin language learning process. This research then further conducts the case studies on the good language learners, to find out the method of cognitive strategies used by the good language learners to enhance Mandarin language using ability. The results have shown that, good language learners prefer to learn Mandarin through Mandarin films and pay more attention to the use of Chinese characters in social media than general learners. On the whole, there are not many applications of cognitive strategies for the Malay students, and their awareness of self-directed learning is still weak. Therefore, this study also explores the methods of teachers to assist students in learning.